On Farm Study on the Efficacy of Nutrient Management Treatments on Bt. Cotton - Puniya, Manmohan; Choudhary, L. R.; Bagri, D. K. (International Journal of Environment, Agriculture and Biotechnology, 2024)
A farmer’s participatory field experiment was conducted during two kharif seasons of 2020 and 2021 at farmers’ fields in Mokheri, Bhojka, Kalimali and Phalodivillages of Jodhpur district of Rajasthan on loamy fine to coarse and medium to low in fertility status. To test the OFT on Efficient use of foliar fertilization technology in Bt cotton cropdeeloped by the Junagadh Agriculture University, Gujarat.The study aimed to analyze the performance and adoption of improved new agriculture technology is a crucialaspects under innovation diffusion process and the most important forenhancing agriculture production at a faster rate. These aspect On Farm Trials technology is one of the most powerful tools for assessment and transfer of technology.The present study was find out the production enhancement and economics through On Farm Trials technology of Bt. cottonon farmers’ fields. The technology On Farm Trial recorded additional pooled yield over farmers’ practices under OFTs the seed cotton and stalkyieldsof Bt. cottonwas increased 14.70 and11.48percent over farmers’ practices. Adoption of improvedpackage of practices under OFTs in Bt. cotton cultivation recorded higher B:C ratio 2.19 as compared to farmers’ practices 1.96 and net returns under OFTs was Rs. 69,287 and farmers’ practicesRs 54,287 recorded. Improved technology (OFTs seed cotton and stalk yields was 19.5 and 23.3 q/ha as compared to farmers’ practices 17.0 and 20.9q/ha. Thus, it may be concluded thatuse of fertilizers as per recommendation with foliar spray of WSF 1 % NPK (19:19:19) at flowering, Boll formation and Boll development stages is effective and economical feasible practice in Bt. Cotton of farming community under irrigated conditon of Rajasthan.